Commentary: Building Bonds: Community and Education (LEARNing Landscapes, 2016)
In this interview, Noel Burke describes how his passion for linking community, education, and lifelong learning began early in his career as a teacher and continued throughout his various roles in educational settings. He gives examples of several projects in which he was involved, highlighting both successes and failures. He explains the key factors that promote successful community-education projects and concludes by giving advice to young professors about integrating their research interests in the community.
Keywords: research; community; education; life-long learning; interview